Improving Tourism Management in Wisata Alam Sumber Manis Gombengsari - Adi Mulyadi; Abdurrahman; Indari (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
This paper discusses improving the governance of Sumber Manis natural tourism in the Suko Environment, Gombengsari Village, Banyuwangi Regency. Tourists visiting Sumber Manis have decreased due to the post-covid-19 pandemic in 2021. Therefore, the destination manager and PGRI Banyuwangi University are collaborating with fielding KKN students to help better tourism management. The method used is to design the management of natural tourism spots in Sumber Manis, fitness tourism, and volleyball courts to attract local, national and foreign visitors. The results of tourism spot management show that Sumber Manis nature tourism has increased from 80% local visitors and 20% foreign tourists in 2022.